Question

\[ f(x) = 3x + 4 \quad g(x) = 2x - 3 \] \[ \text{Найдите: } f \circ g(x) \]

Ask by Maxwell Valdez. in Ukraine
Jan 29,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( f \circ g(x) = 6x - 5 \)

Solution

Чтобы найти композицию функций \( f \circ g(x) \), необходимо подставить функцию \( g(x) \) в функцию \( f(x) \). Шаги вычисления: \[ f \circ g(x) = f(g(x)) = f(2x - 3) \] Подставляем \( 2x - 3 \) в \( f(x) = 3x + 4 \): \[ f(2x - 3) = 3(2x - 3) + 4 = 6x - 9 + 4 = 6x - 5 \] Таким образом, \[ f \circ g(x) = 6x - 5 \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

Давайте найдем \( f \circ g(x) \), что означает, что мы сначала применяем функцию \( g \), а затем результат передаем в функцию \( f \). 1. Сначала вычисляем \( g(x) \): \[ g(x) = 2x - 3 \] 2. Теперь подставляем \( g(x) \) в \( f(x) \): \[ f(g(x)) = f(2x - 3) \] 3. Теперь найдем \( f(2x - 3) \): \[ f(x) = 3x + 4 \] Подставим \( 2x - 3 \) вместо \( x \): \[ f(2x - 3) = 3(2x - 3) + 4 \] \[ = 6x - 9 + 4 \] \[ = 6x - 5 \] Таким образом, \( f \circ g(x) = 6x - 5 \).

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy